2020
DOI: 10.48550/arxiv.2010.10163
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Claw U-Net: A Unet-based Network with Deep Feature Concatenation for Scleral Blood Vessel Segmentation

Abstract: Sturge-Weber syndrome (SWS) is a vascular malformation disease, and it may cause blindness if the patient's condition is severe. Clinical results show that SWS can be divided into two types based on the characteristics of scleral blood vessels. Therefore, how to accurately segment scleral blood vessels has become a significant problem in computer-aided diagnosis. In this research, we propose to continuously upsample the bottom layer's feature maps to preserve image details, and design a novel Claw UNet based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…For example, in Germany, a patient must give informed consent to the use of AI in the process of his diagnosis and treatment, which we believe is a good practice. Also, rules that should be fulfilled by the AI-based system, like the Assessment List for Trustworthy Artificial Intelligence (ALTAI) [207][208][209][210], have been formulated. In [211,212], 10 ethical risk points (ERPs) important to institutions, policymakers, teachers, students, and patients, including potential impacts on design, content, delivery, and AI-human communication in the field of AI and metaverse-based medical education, were defined.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in Germany, a patient must give informed consent to the use of AI in the process of his diagnosis and treatment, which we believe is a good practice. Also, rules that should be fulfilled by the AI-based system, like the Assessment List for Trustworthy Artificial Intelligence (ALTAI) [207][208][209][210], have been formulated. In [211,212], 10 ethical risk points (ERPs) important to institutions, policymakers, teachers, students, and patients, including potential impacts on design, content, delivery, and AI-human communication in the field of AI and metaverse-based medical education, were defined.…”
Section: Discussionmentioning
confidence: 99%
“…Few works have also investigated the effectiveness of Transformer layers by integrating them into the encoder of UNet-based architectures in a plug-and-play manner. For instance, Cheng et al [165] propose TransClaw UNet by integrating Transformer layers in the encoding part of the Claw UNet [166] to exploit multi-scale information. TransClaw-UNet achieves an absolute gain of 0.6 in dice score compared to Claw-UNet on Synapse multi-organ segmentation dataset and shows excellent generalization.…”
Section: Hybrid Architecturesmentioning
confidence: 99%
“…( 1) The RT is used to learn texture information. It extracts texture information by an architecture based on Swin-Unet [15] and Claw U-Net [9], which treats Swin Transformer Blocks as encoders, decoders, and bottlenecks. Also, it includes skip connections to get global information of input images for better segmentation performance.…”
Section: A Architecture Overviewmentioning
confidence: 99%
“…The function of skip connection is to fuse the low-level features, which can compensate for the location information and alleviate the loss caused by down-sampling operations. After the appearance of U-Net, many scholars have also proposed lots of methods based on U-Net, which have achieved better segmentation performance, such as SAUNet [4], LinkNet [5], UNet++ [6], UNet 3+ [7], Attention-UNet [8], Claw U-Net [9] and so on. The performance of these methods has demonstrated that CNNs have a notable ability to learn discriminating features, especially textural features.…”
Section: Introductionmentioning
confidence: 99%